Teologi Terjun Bebas: Bahaya Tafsir Alkitab Tanpa Konteks - Rangga, Okta; Balukh, Semy Djulandy (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2025)
The phenomenon of interpreting the Bible without context is increasingly prevalent in the digital era, creating serious dangers for correct theological understanding. This problem is characterized by the congregation's lack of understanding of hermeneutical principles, the influence of individualism, and the impact of social media algorithms that accelerate the spread of erroneous interpretations. This study aims to identify the causes, impacts, and solutions to this phenomenon. The method used is a qualitative-descriptive approach with literature analysis such as theological books, the Bible and scientific journals. The results of the study indicate that the inability to understand the historical-grammatical context, neglect of church tradition, and low awareness of the theological unity of the Bible are the main root problems. This phenomenon contributes to the emergence of deviant teachings, a crisis of authority in interpreting the Bible, and divisions in the church community. The discussion highlights the importance of developing a hermeneutics curriculum, using digital media wisely, and forming a healthy Bible study community. Based on the formulated title, it shows that the dangers of interpreting without context can be minimized through systematic hermeneutical education and church development that is centered on the authority of God's word. This strategic effort is expected to strengthen the spiritual formation of the congregation and maintain the integrity of Christian teachings amidst the challenges of the digital era.